Redox reactions between guanidine electron donors and silver dicyanamide: synthesis of C,N material precursors and coordination polymers - Eberle, Benjamin; Herrmann, Hendrik Hans; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2013)
Reaction of the organic electron donors ttmgb [1,2,4,5-tetrakis(tetramethylguanidinyl)benzene] and tdmegb [1,2,4,5-tetrakis(N,N′-dimethylethyleneguanidinyl)benzene] with two equivalents of silver dicyanamide, Ag(dca), yielded the two salts (ttmgb)(dca)2 (1a) and (tdmegb)(dca)2 (1b). Their relatively high N/C ratios motivated an analysis of their suitability as precursors to C,N materials. The compounds melt at around 200 °C and decompose at 220 (1a) and 245 °C (1b). Reactions of the organic electron donors with an excess of Ag(dca) resulted in coupled redox and coordination reactions, leading finally to coordination polymers with different dimensionalities. The oxidized guanidine units in the polymers are connected through Ag-dca-Ag bridges, leading to stacks of co-planar C6 rings. The resulting cationic networks are neutralized by dca anions or anionic Ag(dca) chains.